Positioning the hip with respect to the COM: Consequences for leg operation. (7th October 2015) - Blickhan, Reinhard; Andrada, Emanuel; Müller, Roy; Rode, Christian; Ogihara, Naomichi
Abstract: In bipedal runners and hoppers the hip is not located at the center of mass in the sagittal projection. This displacement influences operation and energetics of the leg attached to the hip. To investigate this influence in a first step a simple conservative bouncing template is developed in which a heavy trunk is suspended to a massless spring at a pivot point above the center of mass. This model describes the orientation of the ground reaction forces observed in experiments on running birds. In a second step it is assumed that an effective telescope leg with its hip fixed to the trunk remote from the COM generates the same ground reaction forces as those predicted by the template. For this effective leg the influence of hip placement on leg operation and energetics is investigated. Placing the hip directly below, at, or above the pivot point results in high axial energy storage. Posterior placement increases axial losses and hip work whereas anterior placement would require axial work and absorption at the hip. Shifting the hip far posteriorly as observed in some birds can lead to the production of pure extension torques throughout the stance phase. It is proposed that the relative placement of the hip with respect to the center of mass is an important measure to modify effective leg operation with possible implications for balancing the trunk and the control of legged motion systems. Graphical abstract: Highlights: Conservative template for running with trunk and a pivot point. Dimensionless formulation facilitates comparative analysis. Forces generated by the template are mapped to telescopic legs with hip displaced from the COM. Hip placement strongly affects net axial work, elastic storage and hip work. The template can be used as a framework for future investigation of leg segmentation.